2021
DOI: 10.3390/pharmaceutics13091452
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in ROS-Sensitive Nano-Formulations for Atherosclerosis Applications

Abstract: Over the past decade, ROS-sensitive formulations have been widely used in atherosclerosis applications such as ROS scavenging, drug delivery, gene delivery, and imaging. The intensified interest in ROS-sensitive formulations is attributed to their unique self-adaptive properties, involving the main molecular mechanisms of solubility switch and degradation under the pathological ROS differences in atherosclerosis. This review outlines the advances in the use of ROS-sensitive formulations in atherosclerosis appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…The accumulation of ROS in atherosclerotic endothelial injury promotes macrophage foaming, stimulates their production of pro-inflammatory cytokines and chemokines, and enhances the inflammatory activity of macrophages. Excessive ROS accumulation also induces vascular cell damage, inflammatory cell recruitment, lipid peroxidation, metalloproteinase activation, and extracellular matrix deposition, which together lead to vascular remodeling [ 30 ] [ 31 ]. Nitric oxide (NO) is a multifunctional signaling molecule, which has a number of intracellular effects that lead to vasorelaxation, endothelial regeneration, inhibition of leukocyte chemotaxis, and platelet adhesion [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of ROS in atherosclerotic endothelial injury promotes macrophage foaming, stimulates their production of pro-inflammatory cytokines and chemokines, and enhances the inflammatory activity of macrophages. Excessive ROS accumulation also induces vascular cell damage, inflammatory cell recruitment, lipid peroxidation, metalloproteinase activation, and extracellular matrix deposition, which together lead to vascular remodeling [ 30 ] [ 31 ]. Nitric oxide (NO) is a multifunctional signaling molecule, which has a number of intracellular effects that lead to vasorelaxation, endothelial regeneration, inhibition of leukocyte chemotaxis, and platelet adhesion [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In cardiomyocyte mitochondria, and increased ROS leads to the loss of mtDNA and increased autophagy [91]. Currently, ROS-targeted approaches are the most promising type of anti-atherosclerotic therapies [92].…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“… 332 Previous studies have shown that introduction of exogenous antioxidants into the biological system to scavenge excessive ROS is an effective approach to alleviate and prevent vascular diseases. 333 Additional research evidence has shown that nano-antioxidants have the excellent antioxidant capacity and superior tolerance to harsh microenvironments in comparison to their natural counterparts. 334 Besides, the role of mitochondrial dysfunction in vascular aging encourages the exploration of mitochondrial-targeted therapeutic modalities for the prevention and intervention of vascular aging-related diseases.…”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%